Girl Crazy Based on a Stage Musical by Guy Bolton and Jack McGowan - Gershwin, George; Bolton, Guy; McGowan, Jack (Warner, 2020)
Mickey Rooney stars as a rich party boy called Danny Churchill Jr, who gets packed off by his dad (Henry O'Neill) to an all-male college way out West to stop him being girl crazy. But, once there, he meets the Dean's lovely granddaughter Ginger Gray, played by Judy Garland, along with a Specialty Singer (June Allyson), Polly Williams (Nancy Walker), Dean Phineas Armour (Guy Kibbee), Bud Livermore (Gil Stratton), Henry Lathrop (Robert E Strickland), Rags (Rags Ragland), Marjorie Tait (Frances Rafferty) and Tommy Dorsey's Orchestra. Despite all this top talent here, the delicious, it is the effervescent young star duo Rooney and Garland plus the classy George and Ira Gershwin songs ("Embraceable You", "I Got Rhythm") who have director Norman Taurog's exceedingly pleasant 1943 MGM musical all to themselves. Though Taurog is the credited director, the movie's choreographer Busby Berkeley filmed the climax. "Girl Crazy" is based on Guy Bolton and Jack McGowan’s Broadway stage musical, with the usual considerable cutting and tampering expected when Hollywood gets to work on a show. [www.derekwinnert.com]
Keywords: Blu-Ray-Disc